Processos de extração com solventes GRAS para obtenção de compostos fenólicos a partir de plantas alimentícias não convencionais - Sousa, Ana Carolina Dias de (Universidade Federal de São Carlos, 2025)
Given the contemporary challenges related to food security and sustainability, Non Conventional Edible Plants (PANC) are emerging as strategic alternatives to expand nutritional diversity and promote the responsible use of natural resources. This study aimed to develop and evaluate extraction processes using GRAS solvents (Generally Recognized as Safe) for the recovery of phenolic compounds from purslane (Portulaca oleracea L.), a PANC of high nutritional and functional value. The research was based on a literature review and analysis of recent scientific studies addressing green extraction, bioactive compounds and agro-industrial sustainability. In addition, extraction by maceration and ultrasonic bath was performed using ethanol, water and their mixtures (25, 50 and 75%). The extracts were characterized with respect to total phenolic content. The experimental condition that showed the best performance for the recovery of total phenolics was the use of a 75% hydroalcoholic solvent, yielding 22.45 mg GAE/g of sample. However, ultrasonic-assisted extraction with 75% ethanol for 30 minutes resulted in a slightly higher yield. It was observed that the use of GRAS solvents, such as ethanol and hydroalcoholic mixtures, is an efficient and environmentally safe alternative capable of preserving bioactive molecules while reducing environmental impacts. The results indicate that purslane presents high phenolic content, establishing itself as a promising source for the formulation of functional foods, cosmetics and natural pharmaceuticals. It is concluded that sustainable extraction processes represent an essential tool for the valorization of PANC and the strengthening of the bioeconomy, and further experimental studies are recommended to optimize operational parameters and validate the extraction efficiency obtained.
GRAS solvent extraction processes for obtaining phenolic compounds from unconventional food plants
Keywords: PANC; Portulaca Oleracea; Beldroega; Solventes GRAS; Compostos fenólicos; Extração verde; Purslane; GRAS solvents; Phenolic compounds; Green extraction; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS; 2. Fome Zero e Agricultura Sustentável; 3. Saúde e Bem-Estar